2017
DOI: 10.1088/1361-6439/aa73eb
|View full text |Cite
|
Sign up to set email alerts
|

Design of a collector shape for uniform flow distribution in microchannels

Abstract: The focus of this study is the design of a collector with the objective of achieving uniform flow in multiple parallel microchannels. This objective is achieved by understanding the limitations of current designs and a novel design is proposed, which is further carefully optimized. The existing collector shape considered is U-type, which is investigated numerically. The creation of a stagnation zone, growth of a boundary layer along the collector wall and low/high velocity zones in the collector are identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The tortuosity is represented by τ(À). Tortuosity is one of the predominant variables for the flow across a packed geometry (randomly filled with the uniformly shaped particles) can be estimated by Equation (19). 40 τ…”
Section: Velocity Distribution Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The tortuosity is represented by τ(À). Tortuosity is one of the predominant variables for the flow across a packed geometry (randomly filled with the uniformly shaped particles) can be estimated by Equation (19). 40 τ…”
Section: Velocity Distribution Modelmentioning
confidence: 99%
“…Chein and Chen 18 investigated flow distributions in five geometric header configurations and concluded that the U and V‐type header produced more uniform flow. Siddique et al 19 did a numerical investigation to improve the flow distribution by utilizing a U‐type header. It was found that the presence of sharp corners, which act as the stagnation areas of a rectangular header, was the main reason for nonuniform flow distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The copper block is inserted inside a Teflon block on which inlet and outlet plenum are machined as illustrated in exploded view of test section in figure 1. The plenum is fabricated in the dumbbell shape having the same depth as the microchannel depth which ensures an equal single-phase flow distribution in the channels [9]. A transparent polycarbonate cover (12 mm thick) is fixed on the top of the Teflon copper block.…”
Section: Test Section Design and Fabricationmentioning
confidence: 99%
“…The microchannel entrance length effects, as well as flow maldistributions [15] play an essential role in CHE performance. Studies made on different type of collectors' shapes showed that the creation of a stagnation zone, the growth of a boundary layer along the collector wall and low/high-velocity zones in the collector are the prime causes of flow maldistribution [16]. The partition foil thickness strongly influenced the CHE thermal effectiveness by affecting the axial conduction [17].…”
Section: Introductionmentioning
confidence: 99%